Age‐specific associations between oestradiol, cortico‐amygdalar structural covariance, and verbal and spatial skills. (13th March 2019) - Nguyen, Tuong‐Vi; Jones, Sherri Lee; Gower, Tricia; Lew, Jimin; Albaugh, Matthew D.; Botteron, Kelly N.; Hudziak, James J.; Fonov, Vladimir S.; Louis Collins, D.; Campbell, Benjamin C.; Booij, Linda; Herba, Catherine M.; et al.
Abstract : Oestradiol is known to play an important role in the developing human brain, although little is known about the entire network of potential regions that might be affected and how these effects may vary from childhood to early adulthood, which in turn can explain sexually differentiated behaviours. In the present study, we examined the relationships between oestradiol, cortico‐amygdalar structural covariance, and cognitive or behavioural measures typically showing sex differences (verbal/spatial skills, anxious‐depressed symptomatology) in 152 children and adolescents (aged 6‐22 years). Cortico‐amygdalar structural covariance shifted from positive to negative across the age range. Oestradiol was found to diminish the impact of age on cortico‐amygdalar covariance for the pre‐supplementary motor area/frontal eye field and retrosplenial cortex (across the age range), as well as for the posterior cingulate cortex (in older children). Moreover, the influence of oestradiol on age‐related cortico‐amygdalar networks was associated with higher word identification and spatial working memory (across the age range), as well as higher reading comprehension (in older children), although it did not impact anxious‐depressed symptoms. There were no significant sex effects on any of the above relationships. These findings confirm the importance of developmental timing on oestradiol‐related effects and hint at the non‐sexually dimorphic role of oestradiol‐related cortico‐amygdalar structural networks in aspects of cognition distinct from emotional processes.